Policies on children and schools during the SARS-CoV-2 pandemic in Western Europe - Soriano-Arandes, Antoni; Brett, Ana; Buonsenso, Danilo; Emilsson, Louise; de la Fuente Garcia, Isabel; Gkentzi, Despoina; Helve, Otto; Kepp, Kasper P.; Mossberg, Maria; Muka, Taulant; Munro, Alasdair; Papan, Cihan; et al. (Frontiers in Public Health, 2023)
During the pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), mitigation policies for children have been a topic of considerable uncertainty and debate. Although some children have co-morbidities which increase their risk for severe coronavirus disease (COVID-19), and rare complications, such as multisystem inflammatory syndrome in children and long COVID, exist, most children only get mild COVID-19. In contrast, consistent evidence shows that mass mitigation measures had enormous adverse impacts on children. A central question can thus be posed: What amount of mitigation should children bear, in response to a disease that is disproportionally affecting older people? In this review, we analyse the distinct child versus adult epidemiology, policies, mitigation trade-offs and outcomes in Western Europe. The highly heterogenous European policies applied to children compared to adults did not lead to significant differences in outcomes. Remarkably, the importance of transmission from school-age children to other age groups remains uncertain, with evidence suggesting that schools often follow, rather than lead, community transmission. Important learning points for future pandemics are summarised.